Effect Of Using Online Games And Social Media On Students' Learning Interest At Smk Muhammadiyah Burau, East Luwu District - Sirajuddin Saleh,; Wikatri,; Sitti Hardiyanti Arhas,; Isgunandar, (Technium Social Sciences Journal, 2023)
This study aims to determine the description of the use of online games, social media, student learning interests, the consequences of the use of online games on student learning interests, the influence of social media use on student learning interests, and the impact of using online games and social media on student learning interests in Muhammadiyah Burau Vocational High School (SMK). To achieve this goal, researchers use information collection methods through questionnaires, observation, and documentation. The information obtained from the results of the study was processed by utilizing quantitative analysis to determine the influence of the use of online games and social media on the learning interest of students at Muhammadiyah Burau Vocational High School (SMK). The results of the experiment proved that if the online game variable is in the high category, the social media variable is in the medium category, while the interest in learning students is in the medium category. Based on the results of the experiment, the relationship between product moment variables and learning interest is moderate, while the relationship between social media variables and student learning interest is high. Based on the results of multiple linear regression analysis, it is concluded that there is a negative and significant influence of online games and social media on the interest in training students at Muhammadiyah Burau Vocational High School (SMK).